BizTalk Server 2004 too hot to handle? where to successfully apply Biztalk Server technology. - Bakker, Loek
Recent trends in IT such as service-oriented architecture (SOA) and Web services, in conjunction with the still-increasing popularity of the .NET framework, put Microsoft's BizTalk Server in the center of attention for CIOs, CTOs, architects and enterprise developers. Apparently everyone who is involved with the Microsoft platform now wants to implement Biz Talk. Frequently we see that BizTalk is not implemented in areas where the benefits of the technology can be maximized. This leads to disappointment about the value of BIzTalk, even though the problem is in the application of the technology instead of in the technology itself. In this article I will point out where, how and when the third generation of BizTalk Server can provide real business value.